Asas certainty dalam mekanisme pembayaran kewajiban perpajakan bea perolehan hak atas tanah dan bangunan - Respati, Riskha Indah; Qurbani, Indah Dwi; Syafi’i, R. Imam Rahmat (University of Merdeka Malang, 2020)
It is necessary to understand how arrangements should be made for the paymentmechanism for BPHTB tax obligations in accordance with certainty principles andreflect legal certainty for taxpayers. There are problems that arise regarding therequest for research and inspection of BPHTB by the tax authorities, namely BapendaMalang City in fulfilling BPHTB tax obligations. In these actions often cause conflictsor problems in their implementation. This type of research used in this reserchis about empircal juriidical research using the statutory approach, conceptual aproach,and case approach. The results in reality research show that Malang City Bapendahas not applied certainty principle in BPHTB tax liability payment mechanismespecially regarding BPHTB research requests and examinations, so that futureregulations refer to Malang City Regional Regulation on BPHTB. DOI: https://doi.org/10.26905/idjch.v11i3.4281.How to cite item: Respati, R., Qurbani, I., Syafi’i, R. (2020). Asas certainty dalam mekanisme pembayaran kewajiban perpajakan bea perolehan hak atas tanah dan bangunan. Jurnal Cakrawala Hukum, 11(3). 323-332.doi:10.26905/idjch.v11i3.4281.